Evaluasi Penerapan Program Protokol Kesehatan dan Vaksinasi di Desa Tonom Kecamatan Dumoga Timur Kabupaten Bolaang Mongondow - Marlina Kaesang; Florence D. J. Lengkong; Helly F. Kolondam (JURNAL ADMINISTRASI PUBLIK, 2023)
This study aims to find out about the success rate of implementing the Covid-19 health protocol and vaccination program for the people in Tonom village. The type of research used in this study is a qualitative research method. The data collection techniques used in this study were observation, interviews, and documentation. There are three indicators used in this study, namely: process, benefits, and impact. The results obtained from this study indicate that the implementation of the health and vaccination protocol program in Tonom village has answered the community's needs regarding the handling and prevention of the Corona Virus (Covid-19), besides that the implementation of these programs has also had an impact on economic recovery, and improved quality of life society that used to get worse due to the pandemic. However, the challenge in this research is the process of distributing vaccines that has not run optimally, this is caused by some people who still ignore recommendations from the government to vaccinate. Keywords: Evaluation, Program Implementation, Health Protocols, Vaccination